Analisis Tingkat Modal Sosial Masyarakat Dalam Pengembangan Pariwisata (Studi Kasus: Kampung Warna-Warni Teluk Seribu) - Kintia, Miftahul; Syafitri, Elin Diyah; Dewanti, Ajeng Nugrahaning; Nugroho, Rizky Arif (Perencanaan Wilayah dan Kota, Institut Teknologi Kalimantan, 2024)
Social capital owned by the community plays a very significant role in improving tourism development, people with high social capital tend to participate more actively to achieve common goals, thus increasing awareness and concern for tourism development. Kampung Warna-Warni Teluk Seribu is one of the tours that developed due to the surrounding community's awareness of their area's potential. Thus, this study aims to determine the condition and level ofccommunity social capital in the development of tourism in Teluk Seribu Colorful Village. The scoring analysis method assisted by the Likert scale is used in this researchbby distributing questionnairessto the community. The results obtained from this study show that the social capital owned by the community of Kampung Warna-Warni Teluk Seribu is included in the high level. The community's high level of social capital will increase their participation in tourism development.